2020
DOI: 10.3390/app10196935
|View full text |Cite
|
Sign up to set email alerts
|

Development of Ti/Ni Nanolayered Structures to Be a New Candidate for Energy Storage Applications

Abstract: Development of electrochemical supercapacitor electrode is the best way to improve the performance and conductivity of the alone materials and support energy storage devices. In this work, cyanate anions have used as building blocks to build series of nanolayered materials based on Ti/Ni layered double hydroxides (LDHs). The structural and morphological characteristics of the prepared Ti/Ni LDHs were examined using different techniques. The electrochemical supercapacitive behavior of the prepared LDHs was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The thermal characteristics of the second sample, CSLDH-1 in nitrogen gas, were determined by DTA, DTG and TGA, as shown in Figure 9a. The total weight loss occurred through four steps, indicating removal of surface water, interlayered water, cyanate anions and nitrate anions, respectively [14,15]. The DTG curve showed clear two peaks for the removal of the interlayered anions.…”
Section: Thermal Analysesmentioning
confidence: 97%
See 3 more Smart Citations
“…The thermal characteristics of the second sample, CSLDH-1 in nitrogen gas, were determined by DTA, DTG and TGA, as shown in Figure 9a. The total weight loss occurred through four steps, indicating removal of surface water, interlayered water, cyanate anions and nitrate anions, respectively [14,15]. The DTG curve showed clear two peaks for the removal of the interlayered anions.…”
Section: Thermal Analysesmentioning
confidence: 97%
“…This phenomenon is in agreement with the results of Xu et al [34] that indicated the outcome of the existence of nitrate ions on the bands of LDH. The shoulder peaks recorded at 2925 cm −1 indicate the stretching OH bonds that are due to the interlayer water molecules and/or produced from the hydrogen bonds formed with cyanate ions [15,26,35,36]. The peak at 1617 cm −1 was due to the bending band of the water molecules [37].…”
Section: Fourier-transform Infrared Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…Titanium nickelide (TiNi) alloys are well-known to exhibit various attractive properties [1], such as resistance to corrosion, biocompatibility, shape memory effect, superelasticity, excellent mechanical performance, and so on [2][3][4]. As such, they are extensively studied and applied in numerous fields of science and engineering, including even such unconventional and new for them areas as supercapacitors [5], sensors and actuators [6] and endodontic instruments [7].…”
Section: Introductionmentioning
confidence: 99%